Environmental sustainability practices in effluent management of fashion manufacturing in developing country: Insights from Bangladesh - Md Shamsuzzaman; Mazed Islam (Cleaner Water)
This study examines the environmental sustainability of three textile factories in Bangladesh with varying levels of LEED certification: Platinum LEED-certified (Factory A), Gold LEED-certified (Factory B), and non-LEED-certified (Factory C). Following LEED standards for water usage and pollution control, both untreated and treated effluents were collected from these factories and subjected to chemical analysis. The findings were assessed against established limits for parameters including Chemical Oxygen Demand (COD), Dissolved Oxygen (DO), Biochemical Oxygen Demand (BOD), Total Dissolved Solids (TDS), Total Suspended Solids (TSS), pH, and color. Effluent samples were collected three times a month, and average values were used in the analysis. The results indicated that LEED-certified factories possess greater capacity for effective water use and treatment system design compared to non-certified factories. Significant increases in key metrics such as BOD, TSS, TDS, turbidity, and pH are recorded across all factories after ETP treatment, demonstrating the efficacy of wastewater treatment techniques. Although initial (untreated) effluent samples from all factories exceeded acceptable standards, post-treatment results for Factories A and B achieved compliance with standard parameters, while Factory C was found to require a comprehensive overhaul to meet environmental sustainability requirements. The research shows that LEED certification greatly inspires factory managers to adopt and execute sustainable practices in manufacturing, water management, and effluent treatment. It highlights the necessity of effective wastewater treatment techniques in reducing environmental impact and meeting compliance with regulations in fashion manufacturing. It also emphasizes the technical constraints faced by non-LEED-certified facilities in Bangladesh. Findings will inspire a wide range of stakeholders, including academics, researchers, and industry practitioners, to emphasize reducing the environmental effect of knit textile production. Furthermore, findings will assist industry practitioners in making viable strategic decisions to improve the environmental sustainability of fashion manufacturing.